Delineating outcomes of patients with diffuse large b cell lymphoma using the national comprehensive cancer network‐international prognostic index and positron emission tomography‐defined remission status; a population‐based analysis. (18th November 2015) - Bishton, Mark J.; Hughes, Simon; Richardson, Faith; James, Eleanor; Bessell, Eric; Sovani, Vishakha; Ganatra, Rakesh; Haynes, Andrew P.; McMillan, Andrew K.; Fox, Christopher P.
Summary: The recently devised National Comprehensive Cancer Network International Prognostic Index (NCCN‐IPI) appears superior to the revised IPI (R‐IPI) in delineating outcome in diffuse large B‐cell lymphoma. We examined the outcome of a population‐based cohort of 223 consecutive patients treated with R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) or R‐CHOP‐like immuno‐chemotherapy between January 2005 and December 2011 by both the NCCN‐IPI and R‐IPI, and further stratified outcome by the achievement of both computerized tomography (CT) and positron emission tomography (PET)‐CT complete remission (CR), with the latter reassessed using blinded central review by an independent nuclear medicine and radiology specialist. The NCCN‐IPI was superior to the R‐IPI in identifying patients at very high risk of systemic and/or central nervous system relapse. Notably, both the NCCN‐IPI and the R‐IPI remained strongly predictive of relapse irrespective of CT or PET‐defined remission status following R‐CHOP. Patients with high‐risk NCCN‐IPI scores (≥6) have a dismal outcome following R‐CHOP therapy regardless of PET‐defined response to R‐CHOP. Moreover, such patients appear refractory to salvage chemotherapy and thus require alternative therapeutic approaches, although age and performance status may, for many patients, preclude the safe delivery of a primary intensified regimen. By contrast, patients with NCCN‐IPI 1–5 who achieve PET‐CR following R‐CHOP have excellent outcomes and may merit reduced follow up frequency.